Analysis of traffic incidents involving Emergency Response Teams of the Voivodeship Emergency Medical Services Independent Public Healthcare Facility (WPR SP ZOZ) in Lublin between 2011 and 2014 - Nowicki, Grzegorz Józef; Woźniak, Kamil; Ślusarska, Barbara; Rudnicka-Drożak, Ewa; Jagniski, Jacek; Bednarski, Jerzy; Kotus, Marzena (Journal of Education, Health and Sport, 2017)
Background: Given the type and environment of the performed work, paramedics may be exposed to a variety of injuries or hazards not only to health, but also to life. As it is well known, going in an "emergency" ambulance poses a real threat to road safety. Aim of the study: Analysis of traffic incidents involving Emergency Response Teams (ZMR) of the Voivodeship Emergency Medical Services Independent Public Healthcare Facility (WPR SP ZOZ) in Lublin between 2011 and 2014. Material and method: The research was conducted by a method of retrospective analysis of documentation, in accordance with the "List of damages and communication events involving the vehicles of WPR SP ZOZ in Lublin in claims for third party liability insurance (OC) and comprehensive coverage (AC)". Results: The analysis of the material showed 140 traffic incidents involving Emergency Response Teams of the WPR SP ZOZ in Lublin. The largest number of traffic incidents were recorded in 2011 - 36.44% (n=51), then in 2012 - 23.57% (n=33). In previous years the number of traffic incidents was: in 2013 - 20.71% (n=29) and in 2014 - 19.28% (n=27). For 140 traffic incidents, a traffic incident was caused by a member of a ZRM team in as much as 59.28% (n=83) of cases. In 20.72% (n=29) of cases of traffic incidents involving ZRM team, they were caused by other road users. The analysis showed that 110 damages to the ambulance were located at the front of the vehicle and 120 - at the back. 1 damage to the inside of an ambulance was recorded, and it was caused by an aggressive patient. Conclusions: The total of 140 traffic incidents involving ZRM teams was observed in the analyzed period between 2011 and 2014, however, the number of events was lower each year. Perpetrators of traffic incidents involving ZRM teams were, first of all, ambulance team members, and then, other road users.